Interplay between non-NMDA and NMDA receptor activation during oscillatory wave propagation: Analyses of caffeine-induced oscillations in the visual cortex of rats. (July 2016) - Yoshimura, Hiroshi; Sugai, Tokio; Kato, Nobuo; Tominaga, Takashi; Tominaga, Yoko; Hasegawa, Takahiro; Yao, Chenjuan; Akamatsu, Tetsuya
Abstract: Generation and propagation of oscillatory activities in cortical networks are important features of the brain. However, many issues related to oscillatory phenomena are unclear. We previously reported neocortical oscillation following caffeine treatment of rat brain slices. Input to the primary visual cortex (Oc1) generates N -methyl-d -aspartate (NMDA) receptor-dependent oscillations, and we proposed that the oscillatory signals originate in the secondary visual cortex (Oc2). Because non-NMDA and NMDA receptors cooperate in synaptic transmission, non-NMDA receptors may also play an important role in oscillatory activities. Here we investigated how non-NMDA receptor activities contribute to NMDA receptor-dependent oscillations by using optical recording methods. After induction of stable oscillations with caffeine application, blockade of NMDA receptors abolished the late stable oscillatory phase, but elicited 'hidden' non-NMDA receptor-dependent oscillation during the early depolarizing phase. An interesting finding is that the origin of the non-NMDA receptor-dependent oscillation moved from the Oc1, during the early phase, toward the origin of the NMDA receptor-dependent oscillation that is fixed in the Oc2. In addition, the frequency of the non-NMDA receptor-dependent oscillation was higher than that of the NMDA receptor-dependent oscillation. Thus, in one course of spatiotemporal oscillatory activities, the relative balance in receptor activities between non-NMDA and NMDA receptors gradually changes, and this may be due to the different kinetics of the two receptor types. These results suggest that interplay between the two receptor types in the areas of Oc1 and Oc2 may play an important role in oscillatory signal communication. Highlights: Caffeine-induced oscillations are generated in the visual cortex. The main components of the oscillations consist of NMDA receptor-dependent waves. Non-NMDA receptor-dependent oscillations underlie and precede NMDA receptor-dependent oscillations. Interplay between the two receptor types may induce stable patterns of oscillatory wave propagation.